Love and Belief in a Just World and Marital Commitment in Financial Infidelity in Iranian Couples - Asadi, Masoud; Jahanbakhshi, Zahra; Mahmoodi, Fatemeh; Chegoonian, Atefe (Journal of Psychosociological Research in Family and Culture, 2024)
Objective: The present study investigated the role of love and belief in a just world and marital commitment in financial infidelity in couples. Methods: The statistical population of this correlational study consisted of 300 married men and women in Isfahan. The research instruments included the Belief in a Just World questionnaire (Satun and Douglas, 2005), the Love Styles questionnaire (Hendrick and Hendrick, 1986), the Marital Commitment questionnaire (Adams and Jones, 1997), and the Financial Infidelity questionnaire (Garbinsky et al., 2020). Results: The results of the study revealed that love style and belief in a just world did not have a significant effect on their financial infidelity. However, belief in a just world significantly affected marital commitment. The results also demonstrated that marital commitment had an inverse and significant effect on financial infidelity. Conclusion: It seems that the results of this study can be used by family therapists, premarital counselors, and family researchers.